ERP SEBAGAI BEBAN, BUKAN SOLUSI: STUDI KASUS KEGAGALAN IMPLEMENTASI ERP PADA SWALAYAN - Muhammad Rasyid Ridho; Ahmad Mustofa; Yusna; Istiyanatul Mahbubah; khoirin azaro (Pusat P2M Politeknik Negeri Batam, 2025)
This research aims to explore the underlying reasons for the unsuccessful implementation of Enterprise Resource Planning (ERP) within a micro, small, and medium-sized enterprise (MSME), namely a convenience store located in Malang. Adopting a qualitative exploratory method, the study gathered data through direct observation and in-depth interviews with both the store owner and staff. The findings reveal that, although top management expressed support, the ERP initiative did not succeed. The main contributing factors were limited employee competencies, inadequate project management, the absence of a well-balanced project team, and resistance to organizational change. In addition, insufficient training programs and low employee motivation led to ERP being regarded as a burden rather than an effective tool. The study emphasizes the critical role of organizational preparedness, especially in terms of managing change and developing human resources, in achieving a successful ERP implementation.